Calcium Intake in Elderly Australian Women Is Inadequate - Meng, X.; Kerr, Deborah; Zhu, K.; Devine, A.; Solah, Vicky; Binns, Colin; Prince, R. (MDPI Publishing, 2010)
The role of calcium in the prevention of bone loss in later life has been well established but little data exist on the adequacy of calcium intakes in elderly Australian women. The aim of this study was to compare the dietary intake including calcium of elderly Australian women with the Australian dietary recommendation, and to investigate the prevalence of calcium supplement use in this population. Community-dwelling women aged 70–80 years were randomly recruited using the Electoral Roll for a 2-year protein intervention study in Western Australia. Dietary intake was assessed at baseline by a 3-day weighed food record and analysed for energy, calcium and other nutrients. A total of 218 women were included in the analysis. Mean energy intake was 7,140 ± 1,518 kJ/day and protein provided 19 ± 4% of energy. Mean dietary calcium intake was 852 ± 298 mg/day, which is below Australian recommendations.Less than one quarter of women reported taking calcium supplements and only 3% reported taking vitamin D supplements. Calcium supplements by average provided calcium 122 ± 427 mg/day and when this was taken into account, total calcium intake increased to 955 ± 504 mg/day, which remained 13% lower than the Estimated Average Requirement (EAR, 1,100 mg/day) for women of this age group. The women taking calcium supplements had a higher calcium intake (1501 ± 573 mg) compared with the women on diet alone (813 ± 347 mg). The results of this study indicate that the majority of elderly women were not meeting their calcium requirements from diet alone. In order to achieve the recommended dietary calcium intake, better strategies for promoting increased calcium, from both diet and calcium supplements appears to be needed.